Factors influencing long term tomato seed production under contract farming - Chalee Gedgaew; Suchint Simaraks; A. Terry Rambo (Forestry Faculty, Universitas Hasanuddin, 2018)
Hybrid tomato seed production under contract farming in Northeast Thailand has been declining after three decades of initial introduction. However, some growers in some villages remain as long-term growers. This study was designed to identify factors influencing their long-term production decision making process. A purposive sampling technique was used to select the study sites and key informants for in-depth semi-structured interviews. Group interviews were conducted to validate the data. The contract hybrid tomato seed production system is a centralized model. It is based on a two-way contractual relationships between the company and the individual grower. The companies specify production systems and produce quality standards at a fixed time and price. They support a complete package of inputs credit, loans and extension services to the growers. Costs of all inputs and loans are deducted from the seed payment. These costs are usually forgiven when the crop fails through no fault of the growers. The growers cannot produce hybrid tomato seeds without a contract due to the proprietary germplasm. The quality of the product and marketing are also controlled by the companies. The companies must depend on the farmers’ knowledge however, for the management and technical skills. Therefore, the companies must allow considerable flexibility and leniency in enforcing the terms of the contracts. As a result, knowledgeable and skillful growers are vital factors in sustaining long term hybrid tomato seed production. Furthermore, grower’s personal characteristics stand out as an important factor for long term production. This is why the companies are lenient and flexible with the growers to sustain their mutual benefit.